Gas-Phase Reactivity of OH Radicals With Ammonia (NH3) and Methylamine (CH3NH2) at Around 22 K - González, Daniel; Ballesteros, Bernabé; Canosa, André; Albaladejo, José; Jiménez, Elena (Frontiers in Astronomy and Space Sciences, 2022)
IInterstellar molecules containing N atoms, such as ammonia (NH3) and methylamine (CH3NH2), could be potential precursors of amino acids like the simplest one, glycine (NH2CH2COOH). The gas-phase reactivity of these N-bearing species with OH radicals, ubiquitous in the interstellar medium, is not known at temperatures of cold dark molecular clouds. In this work, we present the first kinetic study of these OH-reactions at around 22 K and different gas densities ((3.4-16.7)×1016 cm-3) in helium. The obtained rate coefficients, with ±2 uncertainties, k1(OH+NH3) = (2.7±0.1)×10-11 cm3 s-1 k2(OH+CH3NH2) = (3.9±0.1)×10-10 cm3 s-1 can be included in pure gas-phase or gas-grain astrochemical models to interpret the observed abundances of NH3 and CH3NH2. We observed an increase of k1 and k2 with respect to those previously measured by others at the lowest temperatures for which rate coefficients are presently available: 230 K and 299 K, respectively. This increase is about 380 times for NH3 and 20 times for CH3NH2. Although the OH+NH3 reaction is included in astrochemical kinetic databases, the recommended temperature dependence for k1 is based on kinetic studies at temperatures above 200 K. However, the OH+CH3NH2 reaction is not included in astrochemical networks. The observed increase in k1 at ca. 22 K does not significantly change the abundance of NH3 in a typical cold dark interstellar cloud. However, the inclusion of k2 at ca. 22 K, not considered in astrochemical networks, indicates that the contribution of this destruction route for CH3NH2 is not negligible, accounting for 1/3 of the assumed main depletion route (reaction with HCO+) in this IS environment.